Colposcopic Findings and Diagnosis in Low-Income Brazilian Women with ASC-H pap Smear Results - Maffini, Cibele Feroldi; Collaço, Luiz Martins; Sebastião, Ana Paula Martins; Zanine, Rita Maira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To determine the accuracy of colposcopy findings in diagnosing cervical intraepithelial neoplasia (CIN) in women with an atypical squamous cells, cannot exclude high-grade squamous intraepithelial lesion (ASC-H) pap smear result and analyze whether the prevalence of HSIL and cancer correlates with sociodemographic risk factors and specific colposcopic findings.Methods Colposcopic findings and sociodemographic risk factors were analyzed as possible predictors of a CIN 2 or worse diagnosis in women with an ASC-H pap smear result.Results Accuracy of the colposcopic impression was 92%, sensitivity was 91.6%, and specificity was 93.1%, with a positive predictive value of 96.4% and negative predictive value of 84.3%. Diagnosis of CIN 2 or worse was more frequent in patients with a previous history of cervical dysplasia and pre-menopausal patients. Identification of major colposcopic findings, dense acetowhite epithelium, coarse mosaicism, and punctuation correlated significantly with CIN 2 or worse.Conclusion Colposcopy performed by an experienced examiner can accurately differentiate patients with CIN 1 or less from patients with CIN 2 or worse. Diagnosis of CIN 2 or worse was more frequent in patients with a previous history of cervical dysplasia and pre-menopausal patients. The degree of acetowhite changes was the best colposcopic feature to predict CIN2 or worse.
Keywords: colposcopy; cervical intraepithelial neoplasia; cervical cancer; ASC-H; cervix uteri